Juridical Review of the Mechanism of Election of Heads Area in Area Special Yogyakarta ( Perspective Democracy and Historical ) - Kelik Endro Suryono; Vicki Dwi Purnomo (Formosa Journal of Social Sciences (FJSS), 2023)
Indonesia is a democratic country, hence the constitution Indonesia in a manner fundamentals confess And ensure sovereignty on actually belongs to the people. This is stated in Article 1 paragraph (2) UUD 1945, that "sovereignty is in the hands of the people, and implemented according to the law Basic . The purpose of this study is to study the Juridical Review of Regional Head Elections in the Special Region of Yogyakarta by conducting research methods. This research is a qualitative research, with the type of research yang used is study References ( libraries research )